NON-ENGLISH STUDENTS ‘ATTITUDES TOWARDS LEARNING SPEAKING - Wulida Makhtuna (BASIS (Bahasa dan Sastra Inggris), 2021)
The issue addressed in this research was attitudes of students taking non-English major towards English learning, especially speaking. The study involved 39 students from a compulsory English class at STKIP PGRI Banjarmasin. The data were collected through questionnaires and interviews. The questionnaires were arranged to reveal students’ attitudes in three components namely affective, behavioral, and cognitive components. The interviews were conducted to clarify and strengthen the findings from the questionnaires. The results of study showed gaps between affective - cognitive components and behavioral one. Most participated students had positive attitudes towards English learning as seen from the affective and behavioral components; however, their behavioral attitudes showed otherwise. Students’ behavioral attitudes were still negative towards learning speaking. These positives attitudes were caused by several reasons including their career aspirations and awareness of the importance of English. Furthermore, the negative attitudes were caused by their study priorities and other personal reasons. In conclusion, what they felt and believed about English did not match their efforts to study the language.